Total Synthesis of Talatisamine. (19th November 2019) - Kamakura, Daiki; Todoroki, Hidenori; Urabe, Daisuke; Hagiwara, Koichi; Inoue, Masayuki
Abstract: Talatisamine (1 ) is a member of the C19 ‐diterpenoid alkaloid family, and exhibits K + channel inhibitory and antiarrhythmic activities. The formidable synthetic challenge that 1 presents is due to its highly oxidized and intricately fused hexacyclic 6/7/5/6/6/5‐membered‐ring structure (ABCDEF‐ring) with 12 contiguous stereocenters. Here we report an efficient synthetic route to 1 by the assembly of two structurally simple fragments, chiral 6/6‐membered AE‐ring 7 and aromatic 6‐membered D‐ring 6 . AE‐ring 7 was constructed from 2‐cyclohexenone (8 ) through fusing an N‐ethylpiperidine ring by a double Mannich reaction. After coupling 6 with 7, an oxidative dearomatization/Diels–Alder reaction sequence generated fused pentacycle 4 b . The newly formed 6/6‐membered ring system was then stereospecifically reorganized into the 7/5‐membered BC‐ring of 3 via a Wagner–Meerwein rearrangement. Finally, Hg(OAc)2 induced an oxidative aza‐Prins cyclization of 2, thereby forging the remaining 5‐membered F‐ring. The total synthesis of 1 was thus accomplished by optimizing and orchestrating 33 transformations from 8 . Abstract : Wie ein Sechser im Lotto : Die hoch oxidierte und kompliziert verknüpfte hexacyclische Struktur (ABCDEF‐Ring) von Talatisamin mit 12 benachbarten Stereozentren stellt eine Herausforderung für die chemische Synthese dar. Eine effiziente Strategie, in der der gesamte Hexacyclus aus einem chiralen AE‐Ringfragment und einem aromatischen D‐Ring zusammengesetzt wird, führt zur Totalsynthese von Talatisamin in 33 Schritten aus 2‐Cyclohexenon.